Targeting the TLR4 axis with microbiota-oriented interventions and innovations in diabetes therapy: a narrative review - Nikolaidis, Christos G.; Gyriki, Despoina; Stavropoulou, Elisavet; Karlafti, Eleni; Didangelos, Triantafyllos; Tsigalou, Christina; Thanopoulou, Anastasia (Frontiers in Immunology, 2025)
The gut microbiota–Toll-like receptor 4(TLR4)–nuclear factor kappa B(NF-κB) signaling is a key controller of low-grade chronic inflammation and insulin resistance in type 1 (T1DM) and type 2 diabetes mellitus (T2DM). While TLR4-mediated inflammation contributes to both T1DM and T2DM, the bulk of microbiota-targeted interventions have been studied in T2DM. The focus of the current review is on T2DM, with relevant parallels in T1DM noted where appropriate. Modulation of this pathway by dietary natural bioactive molecules, fecal microbiota transplantation (FMT), and technological innovations hold therapeutic promise for the reconstitution of metabolic and immune homeostasis. Agents like celastrol, berberine, paeoniflorin, and licorice extract exhibit anti-inflammatory and antidiabetic effects by TLR4/Myeloid differentiation primary response 88(MyD88)/NF-κB signaling inhibition. FMT enhanced β-cell function and insulin sensitivity with evidence of immune-metabolic modulation. New technologies, like ingestible biosensors and gut-on-chip platforms, allow real-time monitoring and precision modulating of the microbiota. Gastric bypass-induced microbial remodeling is linked to long-term glycemic benefit. Pharmacological, surgical, and technological manipulation of gut microbiota–immune interactions is a potential complementary strategy to diabetes. The future encompasses personalized microbiota-matching, controlled FMT regimens, and incorporation of digital therapeutics into microbiome-based precision medicine.